TINGKAT PENDIDIKAN DAN PENDAPATAN ORANGTUA TERHADAP MINAT MELANJUTKAN STUDI KE PERGURUAN TINGGI - Siti Halimah; Mahmu’ddin Mahmu’ddin; Sintia Purwanti (STKIP MUHAMMADIYAH SAMPIT, 2018)
The level of education and parental income affects the interest of the students continue their studies to a higher level, parents who have a background of good education and have a high income, will always give a good motivation for their children to continue their studies to a higher level , This study aims to determine the effect of parental education and income levels of the interest to continue their studies to university. The population in this study were all students of class XII in SMAN 3 Sampit in the academic year 2015/2016, amounting to 262 students, which is then taken 66 students as sample in this study. The approach used is correlational research. The results showed that partially there is no influence of parental educational level of the interest of the students to continue their studies to university while the level of parental income significantly affect interest to continue their studies to university. Simultaneously, there was the influence of parents' education and income levels against the interest of the students to continue their studies to university